A major tool for afforestation of semi-arid and anthropogenic steppe areas in Turkey: Pinus nigra J.F. Arnold subsp. pallasiana (Lamb.) Holmboe - Ayan, Sezgin; Yücedag, Cengiz; Simovski, Bojan (Czech Academy of Agricultural Sciences, 2021)
In Turkey, almost half of which has semi-arid conditions, steppe areas have continuously been increasing. These areas need to be afforested to prevent desertification. For this purpose, this research presents specifically the Anatolian black pine (Pinus nigra J.F. Arnold subsp. pallasiana /Lamb./ Holmboe) as a suitable forest tree species for afforestation activities, due to wide distribution both in Turkey and the broader region. After a thorough investigation of past and recent literature, and onsite activities, the review focuses on the production of seeds and seedlings of the species, land preparation and planting technique, post-planting site maintenance, success in the afforestation areas and considerations on Anatolian black pine seed transfer regioning. In conclusion, local ecological conditions regarding the species should always be taken into consideration. Another important issue for the success of afforestation in semi-arid lands is that the preparation activities of the land for afforestation are carried out with appropriate techniques timely and painstakingly. Moreover, after the 2000s, Turkish forestry focused on afforestation in semi-arid and anthropogenic steppe areas. Anatolian black pine is the most widely used tree species in semi-arid lands and anthropogenic areas and plays the major role in successful afforestation.
Keywords: anatolian black pine; extreme conditions; seed transfer region; Forestry; seedling; SD1-669.5; 2. Zero hunger; 15. Life on land